PENGARUH INDEK PEMBANGUNAN MANUSIA DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP PERTUMBUHAN EKONOMI DI KOTA LHOKSEUMAWE - Hendri Hendri; Fauzan Fauzan; Bobby Rahman (LPPM STIE Lhokseumawe, 2019)
Economic growth is a process of long-term per capita output growth that ccurs when there is a tendency (per capita output to rise) sourced from the internal processes of the economy (the forces within the economy itself), not from outside and temporary. Or in other words self-generating, which means that the growth process itself produces a force or momentum for the continuation of that growth in subsequent periods. This study aims to determine the effect of Human Development Index and Open Unemployment Rate, on economic growth in Lhokseumawe City. This study uses secondary data for 10 years from 2006-2015. Data analysis method used in this research is Ordinary Least Square (OLS). The data used in this research is time series data from 2006-2015. The results of this study indicate that the variables of human development index (X1) have a positive and significant effect on (Y) Economic growth in Lhokseumawe city and Open Unemployment Rate (X2) has no positive and insignificant effect on economic growth (Y) in lhokseumawe city. Keywords: Human Development Index, Open Unemployment Rate, Economic rowth Rate